IMPLEMENTASI FUNGSI LEGISLASI DPRD DALAM PEMBENTUKAN PERATURAN DAERAH (KAJIAN DI BADAN PEMBENTUKAN PERATURAN DAERAH DPRD PROVINSI KALIMANTAN TENGAH): The Implementation of Legislation Function of Regional Representative Council in the Formation of Regional Law (a Study in Regional Law Formation Committee of Central Kalimantan Regional Representative Council) - Sudarsono; Riban Satia, Muhammad; Yusuf, Muhammad (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The legislative function is one of the functions attached to the Regional Representative Council whose main task is to compile regional legal products in the form of Regional Law. The legislative function of this Regional Representative Council needs to be optimized because it is a representation of policy formulation based on the aspirations of the people (bottom-up policymaking). This study aims to examine how the implementation of the legislative function inherent in the Central Kalimantan Regional Representative Council in the process of forming Regional Law and the obstacles that occured. This study uses qualitative methods with data collection techniques through in-depth interviews and observation. The results of the study show that the Central Kalimantan Regional Representative Council carries out its legislative function through the stages of forming Regional Law. Some of the problems found in the process of forming the Regional Law were the absence of a Regional Law Needs Analysis. The other obstacles found were: 1) communication problems with other stakeholders; 2) the organizational structure in Regional Representative Council is inadequate in overseeing various fields; 3) the condition of human resources, including the members, staff and experts who still do not support the optimization of the legislative function; and 4) the role of the Regional Law Formation Committee which still does not have a main place in the Regional Representative Council.